2019
DOI: 10.22159/ajpcr.2019.v12i3.30378
|View full text |Cite
|
Sign up to set email alerts
|

Estimation the Antibacterial Effect of Curcumin and Rosemary Among Patients With Dental Caries in Vitro

Abstract: Objective: The aim is to estimate the effect of curcumin and rosemary as antibacterial agents among dental caries cases. Methods: Samples of saliva were randomly collected from 40 patients in Al-Furat General Hospital who attended the hospital from July to September 2018. Swabs were cultured on blood agar at 37°C for 24 h and then subcultured in mannitol salt agar and trypticase soy broth at 37°C for 24 h. Different concentrations of aqueous extract curcumin solution (0.1, 0.3, 0.5, and 1 mg/ml) and rose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…photodynamic therapy, 27 as well as when compared with Aloe vera and Nutmeg 28 and with Chlorhexidine. 29 The antibacterial effect of methanol Curcumin extracts against S. mutans and Streptococcus pyogenes, 30 and aqueous Curcumin extract against S. mutans as well as Staphylococcus aureus, and anaerobic bacteria 31 has been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…photodynamic therapy, 27 as well as when compared with Aloe vera and Nutmeg 28 and with Chlorhexidine. 29 The antibacterial effect of methanol Curcumin extracts against S. mutans and Streptococcus pyogenes, 30 and aqueous Curcumin extract against S. mutans as well as Staphylococcus aureus, and anaerobic bacteria 31 has been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in vitro have determined its ability to inhibit the cyclooxygenase-2 (COX-2) and nuclear factor-kappa B (NF-κB) gene expression in oral premalignant cancer. Chronic exposure to mutagens developed the reactive oxygen species and inflammation resulting in irregular activation of NF-κB and development of OSCC [64,65] . Rai et al in 2010 [66] demonstrated the antioxidant activity of curcumin by oral leukoplakia, increasing salivary as well as serum concentrations of vitamin C and E in lichen planus and submucous fibrosis patients.…”
Section: Curcuminmentioning
confidence: 99%